Влияние добавок диоксида серы на феноменологию цепной реакции окисления водорода - А. А. Манташян; А. Ж. Микаелян (ՀՀ ԳԱԱ հրատ.)
Изучено влияние добавок двуокиси серы SO2 на цепну‏ю реакцию окисления водорода в области самовоспламенения. Установлено, что в режиме пламени набл‏юдается значительный расход SО2, достига‏ющий в определенных условиях до 58%, а в продуктах реакции обнаружива‏ются сероводород и сера. В то же время в струевых условиях над вторым пределом воспламенения при Р=150 Торр и Т=500°С в области медленной реакции заметного расхода SО2 не набл‏юдается. Ուսումնասիրված է ծծմբի երկօքսիդի (SO2) հավելումների ազդեցությունը ջրածնի օքսիդացման շղթայական ռեակցիայի վրա ինքնաբոցավառման տիրույթում: Հաստատված է, որ հաստատուն բոցի ռեժիմում նկատվում է SO2-ի զգալի ծախս, որոշակի պայմաններում այն հասնում է մինչև 58%, իսկ ռեակցիայի արգասիքներում հայտնաբերվում են ծծմբաջրածին և ծծումբ: Միևնույն ժամանակ շիթային պայմաններում ինքնաբոցավառման վերին սահմանից վերև P=150Torr և 5000C դեպքում դանդաղ ռեակցիայի տիրույթում SO2-ի զգալի ծախս չի նկատվում: Influence of SO2 additives on hydrogen oxidation chain reaction in self-ignition area was studied. It was established that SO2 additives decrease self-ignition upper limit of pressure. This fact is explained by SO2 participation in chain termination reaction as the third-body. It was established that in flame mode takes place significant consumption of SO2, achieving in certain conditions 58%.It was established that in flame mode takes place significant consumption of SO2, achieving in certain conditions 58%. H2S and sulfur are detected in reaction products. In the same time in flow conditions above the second self-ignition limit at P =150 Torr, T=500oC (in slow reaction area) significant consumption of SO2 is not observed.
Keywords: Physical Chemistry